Advertising redefined by new media : a case study of Vodacom South Africa - Muridzo, Searchmore (My University, 2014)
The purpose of this study was to explore if new media have redefined Vodacom SA‟s advertising and if so to what extent. The research employed Vodacom SA as its case study. Quantitative and qualitative descriptive and explorative research was conducted to determine whether the new media had redefined advertising culture and if so to what extent. Data collection was collected through structured questionnaires, the administration of an intensive interview and secondary data. The structured questionnaires were filled in by 200 conveniently randomly selected University of Limpopo students who represented media audiences and their perceptions. The intensive interview was carried out with Vodacom SA‟s Senior Communications officer Ashleigh Dubbelman. The secondary data was collected from Vodacom SA‟s official documents. The research findings revealed that audience interactivity, due to the new media, has become an important aspect of Vodacom SA‟s advertising process. The uses and gratifications theory proved relevant as the research showed that it is not always how the media influences an audience but what the audience responds to media content or messages. Audience preferences and medium selection proved decisive. Social networks, proved to be the new dominant platform for new media advertising. Furthermore, the findings showed that traditional media TV still possess great influence. The digital divide amongst and within audiences were influential in the limited usage of new media in advertising in the Vodacom SA context. In terms of legislation; no explicit laws on new media and advertising have been enacted yet. On advertising expenditure, budgets have remained largely unchanged but allocation increases tilted towards new media. Conclusively; the research observed that new media has redefined Vodacom SA‟s adverting culture, though the redefinition is still minute and is to a small extent. Key Words New media, Vodacom SA, advertising culture, interactivity, digital divide, audience, social networking sites, redefinition, traditional media, uses and gratifications.
Thesis (M.A. (Media Studies)) --University of Limpopo, 2014
Keywords: New media; Advertising culture; Advertising -- South Africa.; Advertising media planning -- South Africa.; Mass media --South Africa.